To simplify the expression
\[ \frac{(4^3 \cdot 7^{-2})^{-5}}{7^9 \cdot 4^{-13}} \]
we will use properties of exponents. First, we will simplify the numerator and the denominator separately.
Step 1: Simplify the Numerator
The numerator is \((4^3 \cdot 7^{-2})^{-5}\). We apply the power of a product property: \((a \cdot b)^n = a^n \cdot b^n\).
\[ (4^3 \cdot 7^{-2})^{-5} = (4^3)^{-5} \cdot (7^{-2})^{-5} \]
Using the power of a power property: \((a^m)^n = a^{m \cdot n}\):
\[ (4^3)^{-5} = 4^{-15} \quad \text{and} \quad (7^{-2})^{-5} = 7^{10} \]
So the numerator simplifies to:
\[ 4^{-15} \cdot 7^{10} \]
Step 2: Simplify the Denominator
The denominator is \(7^9 \cdot 4^{-13}\). We keep it as it is for now because we'll deal with it when we combine the expression.
Now putting it together, we rewrite the full expression:
\[ \frac{4^{-15} \cdot 7^{10}}{7^9 \cdot 4^{-13}} \]
Step 3: Combine the Fraction
Now we can combine the fractions by subtracting the exponents:
\[ = \frac{4^{-15}}{4^{-13}} \cdot \frac{7^{10}}{7^9} \]
Using the exponent subtraction property: \(\frac{a^m}{a^n} = a^{m-n}\):
\[ = 4^{-15 - (-13)} \cdot 7^{10 - 9} \]
Calculating the exponents:
\[ = 4^{-15 + 13} \cdot 7^{1} \]
So, we have:
\[ = 4^{-2} \cdot 7^{1} \]
Step 4: Change to Positive Exponents
Now we express \(4^{-2}\) as a positive exponent:
\[ = \frac{7^{1}}{4^{2}} = \frac{7}{4^2} \]
Calculating \(4^2\):
\[ = \frac{7}{16} \]
Final Answer
Thus, the final simplified expression is:
\[ \frac{7}{16} \]